Social media usage by open education faculties: Atatu University case - Elitas, Turker (Elsevier Science Bv, 2015)
Social media, which provide to sharing of resources irrespective of physical space and time in terms of individual and institutional practices, has been important assistant element. The universities, which include tuition activity among essential functions, whack up course contents and information with students using social media. Especially, universities which include open education faculty defined as distance education, thanks to social media examine and evaluate student without attendance. (C) 2015 The Authors. Published by Elsevier Ltd.
International Educational Technology Conference IETC -- SEP 03-05, 2014 -- Chicago, IL
Keywords: Social Media; Open education Faculty